PENDAMPINGAN PENGEMBANGAN WAWASAN EKONOMI JEMAAT GEREJA BETHEL INDONESIA TABGHA BATAM CENTER MELALUI SISTEM KOPERASI TCOOL BATAM - Gomgom Purba; Suhendra; Donal Pangihutan (JURNAL BEATITUDES, 2022)
Cooperatives based on Christian values ​​need to be present and have an impact to advance the development of the people's economy, the development of cooperatives is aimed at the growth of a positive culture and image as well as strengthening cooperative institutions so that they are able to play a role as a forum for community activities. The COVID-19 pandemic has had an economic impact on the Bethel Church of Indonesia Tabgha Batam Center as the smallest unit in society. The congregation has the risk of not being able to survive to maintain its survival. Family needs that continue to increase and must be met as well as costs for education, health and other operational costs are increasingly limited. If they are unable to survive, the church congregation has the potential to experience a declining level of welfare. The purpose of carrying out this community service is to provide assistance in developing the economic insight of the Indonesian Bethel Church Tabgha Batam Center congregation. This activity has been carried out in 2021 at the Indonesian Bethel Church Tabgha Batam Center. The method used is counseling about the economic development of the congregation through the TCool cooperative, monitoring and involvement of the congregation in the TCool cooperative. All stages have been carried out properly supported by high church participation.